Pemberian Motivasi dan Inspirasi sebagai Bentuk Pendidikan Karakter Generasi Muda dalam Mewujudkan Indonesia Emas 2045 - Albert Albert; Meriyawaty Amelia Prasetio; Kevin Putra Elbistian; Steffanny Halim; Marco Angkasa; Justin Sebastian William; Syechan Almahdaly; Zivanka Gonawi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This study aims to examine the effectiveness of providing motivation and inspiration as a form of character education for the young generation in realizing Indonesia Emas 2045, with a case study at Betlehem Orphanage, Bandar Baru. The background of this study lies in the urgent need to prepare Indonesia’s youth as the nation’s future leaders, who must embody resilience, discipline, and integrity in order to contribute meaningfully to the country’s golden era vision. The research employed a descriptive qualitative approach through the implementation of a motivational seminar attended by 44 foster children. Data were collected using observation, interviews, and documentation during the activity. The findings reveal that the seminar had a significant positive impact, as evidenced by the increased motivation to learn, greater enthusiasm for achieving personal goals, enhanced discipline, and the development of core character values such as responsibility, self-confidence, and teamwork. These outcomes indicate that providing structured motivation and inspiration can serve as an effective strategy for strengthening character education among youth, particularly those from vulnerable backgrounds. Furthermore, the study contributes to the broader discourse on educational innovation by demonstrating how non-formal initiatives, such as motivational seminars, complement formal education in fostering holistic character development. The practical implication suggests that similar programs should be continuously promoted in orphanages, schools, and other educational institutions as part of sustainable efforts to build a generation that is not only academically capable but also morally strong and socially responsible.